2017
DOI: 10.1371/journal.pmed.1002312
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the cost-effectiveness of HIV prevention portfolios for people who inject drugs in the United States: A model-based analysis

Abstract: BackgroundThe risks of HIV transmission associated with the opioid epidemic make cost-effective programs for people who inject drugs (PWID) a public health priority. Some of these programs have benefits beyond prevention of HIV—a critical consideration given that injection drug use is increasing across most United States demographic groups. To identify high-value HIV prevention program portfolios for US PWID, we consider combinations of four interventions with demonstrated efficacy: opioid agonist therapy (OAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 60 publications
0
50
0
Order By: Relevance
“…SSPs provide non-judgmental, free, accessible testing and care services to PWID who often do not have contact with medical services or who shun medical care because of stigma and prior poor treatment [ 53 ]. A recent study found that 50% SSP coverage within the USA would be cost-effective and avert up to 35,000 HIV infections over 20 years [ 54 ]. For maximal impact, SSPs must provide a robust array of health services [ 55 57 ], including HIV testing linked to both primary (e.g., sterile equipment, addiction treatment, PrEP) and secondary HIV prevention (e.g., TasP), and HCV testing with linkage to parallel services.…”
Section: Resultsmentioning
confidence: 99%
“…SSPs provide non-judgmental, free, accessible testing and care services to PWID who often do not have contact with medical services or who shun medical care because of stigma and prior poor treatment [ 53 ]. A recent study found that 50% SSP coverage within the USA would be cost-effective and avert up to 35,000 HIV infections over 20 years [ 54 ]. For maximal impact, SSPs must provide a robust array of health services [ 55 57 ], including HIV testing linked to both primary (e.g., sterile equipment, addiction treatment, PrEP) and secondary HIV prevention (e.g., TasP), and HCV testing with linkage to parallel services.…”
Section: Resultsmentioning
confidence: 99%
“…We searched PubMed from 1 January 2013 to 11 October 2017 with the terms "HIV" AND ("PrEP" OR "PrEP") AND ("cost" OR "costeffectiveness") with the goal of identifying any new studies that have appeared since the 2013 meta-analysis of PrEP cost-effectiveness modelling studies [32]. The search retrieved 149 abstracts, of which 21 provided country-specific estimates of the cost-effectiveness of various PrEP implementation strategies [6,8,9,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. This study is not only the first to provide data and evidence on the costs and cost-effectiveness of providing oral PrEP to MSM in Thailand, but is also the first such study from the Asia-Pacific region.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the characteristics detailed above, individuals are homogenous and cannot be distinguished from one another in the model. Details of transmission calculations and model equations can be found in the Appendix and in the appendix of two previously published analyses ( Bernard et al., 2017 , Bernard et al., 2016 ).…”
Section: Methodsmentioning
confidence: 99%